The Multiple Facets of Code-Switching - Abellana, Caren B; Tarusan, Mary Ann E (Journal of Social Work and Science Education, 2023)
Code-switching (CS) of language teachers is common; however, educators have different views on its purpose and effect on students' learning. With this, there should be a re-examination of the use of code-switching by language teachers in English language classes.  This research aimed to uncover the multiple facets of CS specifically the common types of CS used by teachers, why they code-switch, and the insights they can share with their peers. The researcher made use of the qualitative method, specifically phenomenology. In addition, analyzing the transcription of the video lessons of each participant was also conducted to provide a descriptive data on the types of CS used. The study's results discovered that teachers commonly use intra-sentential and rarely use tag-like CS; they also use inter-sentential occasionally. Moreover, it uncovered those teachers code-switched for easy access of learning, self-convenience, and time constraints. It also draws insights from the teachers, which reveals that CS can make them efficient and innovative while strengthening students' understanding. This qualitative analysis of the multiple facets of code-switching would allow teachers to make informed decisions about whether or not to incorporate code-switching into their language teaching pedagogy.